Предмет: Алгебра,
автор: annnadrebt
упростить выражение (3х+10у)-(6х+3у)+(6у-8х)
Ответы
Автор ответа:
38
(3х + 10у) - (6х + 3у) + (6у - 8х) = 3х + 10у - 6х - 3у + 6у - 8х =
= - 11х + 13у
= - 11х + 13у
Автор ответа:
11
(3x+10y)-(6x+3y)+(6y-8x) =
3x+10y-6x-3y+6y-8x =
13y-11x
3x+10y-6x-3y+6y-8x =
13y-11x
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: vanami
Предмет: Окружающий мир,
автор: netesa0202
Предмет: География,
автор: turtleman49
Предмет: Английский язык,
автор: kseniamakadzeba